Novel fault detection criteria based on linear quadratic control performances - Krokavec, Dušan; Filasová, Anna (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a new approach to designing a relatively simple algorithmic fault detection system that is potentially applicable in embedded diagnostic structures. The method blends the LQ control principle with checking and evaluating unavoidable degradation in the sequence of discrete-time LQ control performance index values due to faults in actuators, sensors or system dynamics.
Keywords: performance degradation; fault detection schemes; discrete-time systems; LQ control methods